Tren dan Korelasi Harga Terhadap Volume Ekspor Komoditas Perkebunan: Studi Data Sekunder 2015-2024 - Khairad, Fastabiqul; Khairad, Merdian (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
Indonesia’s plantation commodity exports play a vital role in the national economy. However, global price dynamics and export volume fluctuations reflect uncertainties that require further investigation. This study aims to analyze (1) the trends of export prices and volumes, (2) the relationship between price and export volume, and (3) the effect of price on export volume for four major commodities: Crude Palm Oil (CPO), cocoa, coffee, and rubber during the period 2015–2024. The research uses secondary data, analyzed through descriptive analysis, Pearson correlation, and simple linear regression. The findings show that both price and export volume trends are volatile, with cocoa prices surging sharply in 2024. Pearson correlation results indicate a negative relationship between price and export volume for all commodities, but only CPO shows a statistically significant result (r = -0.917). The regression analysis confirms this, as CPO price significantly influences its export volume (R² = 0.841; p 0.01). Meanwhile, cocoa, coffee, and rubber show no significant price impact. The study concludes that the sensitivity of export volume to price varies by commodity, thus export policy should be tailored to the characteristics of each plantation product.